Controlled piezotronic properties on recoverable energy storage density in rare-earth ions doped epitaxial PZT thin films. (23rd May 2019) - Rath, Martando; Miryala, Muralidhar; Murakami, Masato; Ramachandra Rao, M S
Abstract: The present study describes the influence of rare-earth (RE = La, Eu, Dy and Ho) ions on recoverable energy storage density in PLD grown epitaxial Pb(Zr x Ti1− x )O3 (PZT) thin films on SRO/LSAT (0 0 1) hetrostructures. Special attention has been paid to remove the pyrochlore phase, which is a prominent unwanted phase in ferroelectric specimens with rare earth dopants. The evidence of single crystallinity of the hetrostructures was confirmed from x-ray diffraction. The presence of single zone points in the Kikuchi patterns in electron back scattering diffraction reveals the epitaxial nature of rare earth doped PZT thin films. In addition, an x-ray photoelectron spectroscopy experiment was carried out to determine the oxidation states after doping the rare-earth ions in the PZT sample. The enhancement of spontaneous polarization in the donor (La, Eu) doped PZT films compared to the pure one is attributed to easy orientation and mobility of domain walls. It is found that the piezoelectric coefficient (d33 ) is more (130 pm V −1 ) for La doped PZT films (La:PZT), compared to the other rare earth doped PZT thin films. In our results, we found asymmetric polarization versus electric field hysteresis loop and energy storage efficiency ( ) values of 30% were recorded in the case of pure PZT film and the value decreased to 28% with Ho doping, however, a high value of 46% could be realized in La:PZT.